Faktor-faktor yang Mempengaruhi Kualitas Hidup Pasien Tinitus di RSUD Provinsi NTB - Primaditha, Dara; Kadriyan, Hamsu; Widiastuti, Ida Ayu Eka (Jurnal Kedokteran, 2012)
Introduction: Based on previous studies in Asia, the incidence of tinnitus was about 10.9%. Tinnitus shows a close association with psychological and social disorders and leads to a decline in quality of life. Most patients complain of sleep disorders, anxiety, and even depression. There are several factors that allegedly affect the quality of life of tinnitus patients such as age, sex and location of tinnitus. This study aims to prove the influence of these factors on the quality of life of tinnitus patients. Method: This is an analytic descriptive research with cross sectional design. The sample of this study was 37 patients tinitus who visited the ENT outpatient clinic of NTB Provincial Hospital that has met the inclusion and exclusion criteria. The respondents then filled out the Tinnitus Handicap Inventory (THI) questionnaire. The data obtained are then tested for validity and reliability, followed by Mann-Withney and Kruskall-Wallis tests to determine the effect of age, sex, and tinnitus on quality of life. Results: Based on the THI score, 86.8% of tinnitus patients experienced quality of life disorders of varying degrees. From the analysis of data about the effect of age on the quality of life, p = 0.957 (p> 0,05) means that there is no difference in the quality of life of tinnitus patients in all four age groups. The test results on the sex variables gave p = 0.430 (p> 0,05), this also means there is no difference in quality of life between men and women. The test of tinnitus location variable gives p value = 0,631 (p> 0,05). This means there is no difference in the quality of life between patients with bilateral and unilateral tinnitus. Conclusion: The quality of life of tinnitus patients is not affected by age, sex, and location of tinnitus.